Tipe Perilaku Impulsive Buying, Etnografi Para Digital Natives - Zsasa Novinda; Emma Yunika Puspasari (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
The existence of increasingly sophisticated digital technology has caused people's activities to experience changes in terms of consumption. Jayabaya's prediction "Yen Pasar Ilang Kumandhange" has a philosophy regarding the change in people's consumption to online. Even though this prediction was created a long time ago, this prediction is in accordance with current market conditions which are increasingly empty of visitors. As a result of these changes, new activities have emerged, namely impulsive buying behavior. This research aims to examine whether Jayabaya's predictive philosophy applies to digital natives, the motives behind groups of digital natives carrying out impulsive buying behavior and to categorize the types of impulsive buying behavior in digital natives. This research approach is a qualitative approach with a realist ethnographic model. The data collection methods used were observation, interviews, digital studies, literature studies and documentation. The analysis used in this research is the Spradley analysis. The research results show (1) Jayabaya's prediction philosophy applies to digital natives, (2) there are several motives behind digital natives' impulsive buying behavior, namely convenience and superiority of the marketplace, product, price, payment method, advertising, surrounding environment, trends, and self-control , (3) most digital natives fall into the planned impulse buying type.